1994
DOI: 10.1016/0008-6223(94)90046-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalytic reduction of no with NH3 over activated carbons. I: Effect of origin and activation procedure on activity

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…As compared to non-doped carbon materials, nitrogen-doped carbon has a higher oxidation resistance. 11,12 Stoehr et al 10 showed that the nitrogen doping by post-treatment in ammonia improved the performance of activated carbon in oxidation reactions. The nitrogen doping also enhanced the basicity of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to non-doped carbon materials, nitrogen-doped carbon has a higher oxidation resistance. 11,12 Stoehr et al 10 showed that the nitrogen doping by post-treatment in ammonia improved the performance of activated carbon in oxidation reactions. The nitrogen doping also enhanced the basicity of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon has a high surface area and an excellent ability for adsorption of diluted molecules and ions in gas and liquid phases. Therefore, it has been widely used in many industrial and domestic processes such as the removal of contaminants, , gas separation, , gas storage, and catalytic reactions. Although activated carbon has a large surface area, the amount adsorbed is mainly dependent on the structure of the pores, particularly micropores. This is because the walls of the pores provide a stronger potential than the external surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, considerable efforts have been devoted to removing NO, selective catalytic reduction (SCR) [7] and NO x storage/reduction (NSR) [8] turning NO x into N 2 are the most developed techniques NO x control technology. Nevertheless, SCR and NSR are only effective in removing high-concentration of NO x at higher working temperature (generally above 200°C), which hinder their application in the removal of lowconcentration NO at room temperature.…”
Section: Introductionmentioning
confidence: 99%